#### Answer

x=$\frac{y+C}{A-B}$

#### Work Step by Step

y=Ax-Bx-C
y=x(A-B)-C
y+C=x(A-B)
$\frac{y+C}{A-B}$=$\frac{x(A-B)}{A-B}$
$\frac{y+C}{A-B}$=x
x=$\frac{y+C}{A-B}$

Published by
Pearson

ISBN 10:
0-13417-805-X

ISBN 13:
978-0-13417-805-9

x=$\frac{y+C}{A-B}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.